Characterisation of oils and fats from seeds of several Malaysian fruits and their enzymatic interesterification - Abdul Manaf, Yanty Noorzianna (2009)
The processing of many fruits results in the accumulation of large quantities of seeds and kernels. Proper utilization of these by-products could reduce waste disposal problems and serves as a potential new source of fats for use in food and non-food systems. To date, a large number of plant seeds have been analyzed and some of these have been cultivated as new oil crops. In this study, the oils/fats from the seeds of honeydew melon iCucumis melo var. inodorus), musk lime (Citrus microcarpa), papaya (Carica papaya L., variety Hong Kong variety) and rambutan (Nephelium lappaceum L.) were extracted and their physico-chemical characteristics determined. Honeydew melon seeds contained 25.0% of oil of which linoleic acid (69.0%) was the dominant fatty acid. It was found to be a rich source of unsaturated fatty acid (86.1 %). Musk lime seeds contained 33.8% oil comprising 73.6% unsaturated fatty acids with linoleic (31.8%) and oleic (29.6%) acids as the predominant fatty acids. The iodine and saponification values of musk lime seed oil (MLSO) were 118.1 g bll 00 g and 192.6 mg KOH/g, respectively. It contained POL (18.9%) as the most prominent TAG, followed by PLL (13.7%) and OLL (11.9%). The complete melting and crystallization transition temperatures of MLSO were lo.rc and -4.2°C, respectively. The oil content of papaya seeds (Hong Kong variety) was 27.0% with oleic acid (73.47%) as the dominant fatty acid followed by palmitic acid (15.8%). It contained 000 (40.4%) as the most prominent TAG followed by POO (29.1 %) and SOO (9.9%). Rambutan seeds contained 38.0% of oil. Compared to oils from the other seeds, oleic (42.0%) and arachidic (34.3%) acids were the dominant fatty acids. Most of TAG peaks have long retention times and could not be identified due to non-availability of required standards. The individual seed oils (honeydew melon, musk lime, papaya and rambutan) and oil blends (rambutan:honeydew melon, rambutan:musk lime, rarnbutan.papaya, honeydew melon:musk lime, honeydew melon:papaya and musk lime:papaya) at I: I ratio were interesterified using three lipases namely Lipozyme 1M, Lipozyme TL and Novozym 435 from Novozyme (Copenhagen, Denmark). The immobilized lipase was added at 0.0 I% (w/w) to 6.0 g of oil in 10 ml of n-hexane. The reaction mixture was then agitated in an orbital shaker at (200 rpm) kept at 40°C for 6, 12, 24 h, where each reaction was carried out in duplicate and a sample without enzyme was used as the control. HPLC analysis showed that several TAGs increase in concentration, while other TAG decreased in concentration as indicated by the increase and reduction in peak areas, respectively. Lipozyme 1M and Lipozyme TL gave increments of similar TAG peaks after interesterification except for musk lime seed oil. Interesterification of musk lime gave increments of similar TAG peaks when Lipozyme TL and Novozym 435 were used. The reduction of some TAG peaks, and formation of acylyglycerol including free fatty acid content during interesterification indicate that hydrolysis also took place, a phenomenon confirming the reversibility of lipase reaction on its substrate before interesterification can take place for all samples. The amount of TAG of all seed oil samples were decreased after 24 h when all three enzymes were used. Novozym 435 gave the highest amount of TAG after interesterification followed by Lipozyme TL and Lipozyme 1M for all oil samples. Lipozyme 1M gave significantly (P<O.05) higher percentage of partial acyl glycerol and free fatty acid content than Lipozyme TL and Novozyrne 435. Thus, Lipozyme 1M showed that it had a highest hydrolytic activity. The interesterification process led to some changes in the heating and crystallization profiles of the seed oils. Peak broadening was seen clearly in honeydew melon seed oil, indicating these changes could possibly be due to the formation of TAG molecular species with wider melting ranges. In heating and cooling profiles of papaya seed oil, the major peak became sharper compared to the original oil, indicating that homogeneity of TAG component was formed. It is most likely due to its high content of 000. Most of the reactions involving all seed oils and oil blends increased the melting temperatures after 24 h of interesterification. It might be due to more formation of saturated TAG. In many cases, interesterification of seed oil blends changed the existing thermal transitions and produced additional peaks. This could be due to the changes in the TAG profile and formation of free fatty acid caused by the enzymatic interesterification.